2009
DOI: 10.1074/jbc.m109.010231
|View full text |Cite
|
Sign up to set email alerts
|

The Interferon Consensus Sequence Binding Protein (ICSBP/IRF8) Activates Transcription of the FANCF Gene during Myeloid Differentiation

Abstract: The interferon consensus sequence binding protein (ICSBP) is an interferon regulatory transcription factor with leukemiasuppressor activity. ICSBP regulates genes that are involved in phagocyte function, proliferation, and apoptosis. In murine models ICSBP deficiency results in a myeloproliferative disorder (MPD) with increased mature neutrophils. Over time this MPD progresses to acute myeloid leukemia (AML), suggesting that ICSBP deficiency is adequate for MPD, but additional genetic lesions are required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(48 citation statements)
references
References 34 publications
2
45
0
1
Order By: Relevance
“…This suggested a possible IRF8-binding cis element between -48 and -56 bp. Consistent with this, the -50 to -56 bp Fancc sequence had homology with an IRF-binding consensus (5′-GAAAAT-3′ compared with the ISRE consensus [5′-GAAANN-3′] and the IRF8-binding Fancf cis element [5′-GAAAGC-3′]) (17,33). We mutated this sequence in the context of the -56-bp Fancc promoter construct (5′-GAAAAT-3′ to 5′-GAACAT-3′) and found that the mutant construct did not exhibit IRF8-induced promoter activity ( Figure 2B).…”
Section: Figurementioning
confidence: 62%
See 4 more Smart Citations
“…This suggested a possible IRF8-binding cis element between -48 and -56 bp. Consistent with this, the -50 to -56 bp Fancc sequence had homology with an IRF-binding consensus (5′-GAAAAT-3′ compared with the ISRE consensus [5′-GAAANN-3′] and the IRF8-binding Fancf cis element [5′-GAAAGC-3′]) (17,33). We mutated this sequence in the context of the -56-bp Fancc promoter construct (5′-GAAAAT-3′ to 5′-GAACAT-3′) and found that the mutant construct did not exhibit IRF8-induced promoter activity ( Figure 2B).…”
Section: Figurementioning
confidence: 62%
“…This set included genes that terminate cytokine-induced proliferation (NF1 and GAS2), increase sensitivity of phagocytes to Fas-induced apoptosis (PTPN13), and are involved in DNA repair (FANCF) (14)(15)(16)(17). We found that IRF8 activated FANCF (the gene encoding Fanconi F) in bone marrow progenitor cells that were stimulated with differentiating cytokines (17).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations